2019
DOI: 10.3390/ijerph16152647
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Individual and Neighborhood Characteristics on Mental Health after a Period of Economic Crisis in the Lisbon Region (Portugal): A Multilevel Analysis

Abstract: Mental health is an intrinsic dimension of health influenced by individual and contextual factors. This cross-sectional study analyzes the association between the individual, neighborhood characteristics, and one’s self-assessed mental health status in the Lisbon region after an economic crisis. Via the application of multilevel regression models, the study assesses the link between one’s neighborhood environment—deprivation, low self-assessed social capital, and low self-assessed satisfaction with the area of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 92 publications
0
14
0
Order By: Relevance
“…This exception might be explained by the geographical scale of this study, the financial instability experienced in Portugal [ 19 , 66 ], and the effect of the economic crisis on suicidal behaviour, which was transversal to all socioeconomic groups of society [ 24 ]. During the last austerity period, Portugal faced repercussions in terms of unemployment, emigration, purchasing power, and inability to afford housing costs [ 37 , 38 , 67 ], which affected both privileged and deprived areas [ 24 ] and, consequently, their access to healthcare [ 68 ]. On the one hand, the private sector lost many clients that were not able to afford their services due to loss of income; on the other, the public sector suffered blind cuts in expenditure, increases in co-payments, and reduced state subsidies for some treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This exception might be explained by the geographical scale of this study, the financial instability experienced in Portugal [ 19 , 66 ], and the effect of the economic crisis on suicidal behaviour, which was transversal to all socioeconomic groups of society [ 24 ]. During the last austerity period, Portugal faced repercussions in terms of unemployment, emigration, purchasing power, and inability to afford housing costs [ 37 , 38 , 67 ], which affected both privileged and deprived areas [ 24 ] and, consequently, their access to healthcare [ 68 ]. On the one hand, the private sector lost many clients that were not able to afford their services due to loss of income; on the other, the public sector suffered blind cuts in expenditure, increases in co-payments, and reduced state subsidies for some treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Previous ecological studies have found an association between a material deprivation composite index and total mortality [ 9 ], premature deaths [ 28 , 30 ], avoidable mortality amenable to healthcare [ 23 ], diabetes [ 31 ], infectious diseases [ 31 ], cancer [ 32 ], dementia [ 33 ], suicide [ 24 ], ischemic heart disease [ 34 ], cancer [ 35 ], cerebrovascular disease [ 36 ], chronic liver disease [ 29 ], and traffic injuries [ 21 ]. In the context of crisis and austerity, these associations tend to increase, as vulnerable populations appear to be more affected by the negative consequences of austerity measures [ 19 , 37 , 38 ]. Nonetheless, studies to date regarding total mortality in several European cities revealed that the 2008 economic crisis did not change this pattern in the short term [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the unemployment rate reached 6.2% in February, 5.9% in March, and 6.0% in April, approximately one percentage point higher than the unemployment rate in the same period last year [ 3 ]. In the context of this economic downturn caused by the COVID-19 pandemic, many working adults are in danger of losing their jobs or having their salaries cut, which may threaten their mental health [ 4 , 5 ]. In addition, their work attitudes may also change accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, improvements in living conditions and the distribution of services have been unequally shared across individuals, groups and geographical areas, with potential health consequences on vulnerable groups. There is indeed growing evidence of associations between residential location in socially deprived areas and a wide variety of health conditions, [1][2][3][4] premature and preventable deaths [5][6][7] and mental health 8 and suicide. 9 Socioeconomically disadvantaged areas are more likely to amplify conditions of material deprivation through a number of underlying interconnected mechanisms, leading to cumulative vulnerabilities 4 : (1) neighbourhoods that concentrate low-income groups with higher potential for poor health outcomes; 10 (2) environments with high exposure to risk factors such as air pollution and road traffic 11 and (3) environments that discourage healthy behaviours, for example, due to low access to green areas, shops and facilities.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, improvements in living conditions and the distribution of services have been unequally shared across individuals, groups and geographical areas, with potential health consequences on vulnerable groups. There is indeed growing evidence of associations between residential location in socially deprived areas and a wide variety of health conditions, 1–4 premature and preventable deaths 5–7 and mental health 8 and suicide. 9 …”
Section: Introductionmentioning
confidence: 99%